An analysis of social problems in Malaysia: the case of Johor - Mohd Amin, Ruzita; Selamah , Abdullah Yusof; Md. Noon, Hazizan; Haneef, Mohamed Aslam (IIUM Press, 2008)
This study looks into the relationship between social problems and what are termed as "internal" and "external" factors. Internal factors relate to characteristics intrinsic to the individuals themselves, while external factors refer to exogenous factors which are not within the control of the individuals under study. The study focuses on two internal factors,namely, the individual's self esteem, and the individual's personality in terms of the factors influencing it. The analysis is done at the micro level on school-going teenagers where the individual's self-esteem is considered to be reflected in the student's self-perception of his/her academic ability. The sample in this study consisted of 2869 randomly selected Forms 1, 3 and 5 students from 10 secondary schools in the state of Johor. Both urban and rural schools were included, and the students were chosen from above average, average and below average classes. This was done to reflect the heterogeneity of the population with respect to age, academic ability, ethnic group, and other factors. Significant findings with regard to social problems including levels of involvement, comparison among ethnic groups, correlation between internal and external factors and others were generated from this study, on the basis of which some recommendations were proposed.